High-Temperature Processing of Food Products Unit Operations and Processing Equipment in the Food Industry - Jafari, Seid Mahdi; Jafari, Seid Mahdi (Woodhead Publishing, 2022)
High-Temperature Processing of Food Products, a volume in the Unit Operations and Processing Equipment in the Food Industry series, explains the processing operations and equipment necessary for high-temperature processing of different food products including frying, baking, roasting, and cooking. These processes and unit operations are very important in terms of achieving favorable sensory properties and energy usage. Divided into four sections, "Cooking Operations," "Baking and Roasting Operations," "Thawing Operations," and "Frying Operations," all the chapters emphasize the fundamentals of experimental, theoretical, and/or computational applications of food engineering principles and the relevant processing equipment to high-temperature unit operations. Written by experts in the field of food engineering, in a simple and dynamic manner, this book targets industrial engineers working in the field of food processing and in food factories to make them more familiar with food processing operations and equipment. - Explores the operations and equipment necessary for high-temperature processing of different food products - Covers various alternatives for high-temperature processing operations, including frying, baking, roasting and cooking - Emphasizes ways to improve the quality and safety of food products with high-temperature processing